Self‐reported previous knee injury and low knee function increase knee injury risk in adolescent female football. Issue 8 (15th July 2015) - Clausen, M. B.; Tang, L.; Zebis, M. K.; Krustrup, P.; Hölmich, P.; Wedderkopp, N.; Andersen, L. L.; Christensen, K. B.; Møller, M.; Thorborg, K.
Abstract : Knee injuries are common in adolescent female football. Self‐reported previous knee injury and low Knee injury and Osteoarthritis Outcome Score (KOOS) are proposed to predict future knee injuries, but evidence regarding this in adolescent female football is scarce. The aim of this study was to investigate self‐reported previous knee injury and low KOOS subscale score as risk factors for future knee injuries in adolescent female football. A sample of 326 adolescent female football players, aged 15–18, without knee injury at baseline, were included. Data on self‐reported previous knee injury and KOOS questionnaires were collected at baseline. Time‐loss knee injuries and football exposures were reported weekly by answers to standardized text‐message questions, followed by injury telephone interviews. A priori, self‐reported previous knee injury and low KOOS subscale scores (< 80 points) were chosen as independent variables in the risk factor analyses. The study showed that self‐reported previous knee injury significantly increased the risk of time‐loss knee injury [relative risk (RR): 3.65, 95% confidence (CI) 1.73–7.68; P  < 0.001]. Risk of time‐loss knee injury was also significantly increased in players with low KOOS subscale scores (< 80 points) in Activities of Daily Living (RR: 5.0), Sport/Recreational (RR: 2.2) and Quality of Life (RR: 3.0) ( P  < 0.05). In conclusion, self‐reported previous knee injury and low scores in three KOOS subscales significantly increase the risk of future time‐loss knee injury in adolescent female football.